2014
DOI: 10.1590/0102-311x00007314
|View full text |Cite
|
Sign up to set email alerts
|

Future burden of prostate cancer mortality in Brazil: a population-based study

Abstract: Prostate cancer mortality projections at the nationwide and regional levels to the year 2025 are carried out in this ecological study that is based on an analysis of Brazilian trends between 1996 and 2010. The predictions were made for the period 2011-2025 utilizing the Nordpred program based on the period of 1996-2010, using the age-period-cohort model. A significant increase was observed in the Brazilian rates between 1996 and 2006, followed by a non-significant decrease. The projections indicate a decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 17 publications
(25 reference statements)
2
16
0
5
Order By: Relevance
“…For the period from 1980 to 2010, there was an upward trend in mortality from the disease to Brazil and all regions, with the northeast showing the highest variation, while the south and southeast showed the lowest 18 . Similarly, analysis of the trend of prostate cancer mortality rates in Brazil and regions in the period 1996 to 2010 showed a significant increase between 1996 and 2006, followed by a non-significant decrease, with an estimate of decrease at national level until the year 2025 and in the Midwest, south, and southeast regions, as opposed to an increase in the north and northeast regions 19 . However, a study that evaluated the burden of the disease in Central and South America found, for Brazil, a practically stable trend in mortality rates between 1997 and 2008 20 .…”
Section: Discussionmentioning
confidence: 95%
“…For the period from 1980 to 2010, there was an upward trend in mortality from the disease to Brazil and all regions, with the northeast showing the highest variation, while the south and southeast showed the lowest 18 . Similarly, analysis of the trend of prostate cancer mortality rates in Brazil and regions in the period 1996 to 2010 showed a significant increase between 1996 and 2006, followed by a non-significant decrease, with an estimate of decrease at national level until the year 2025 and in the Midwest, south, and southeast regions, as opposed to an increase in the north and northeast regions 19 . However, a study that evaluated the burden of the disease in Central and South America found, for Brazil, a practically stable trend in mortality rates between 1997 and 2008 20 .…”
Section: Discussionmentioning
confidence: 95%
“…In Brazil, the distribution of hierarchic levels for patient care is unequal, with high disparities: areas with better urban structures (Southeast and South regions), count with well-equipped and distributed health systems, while the North and Northeast regions suffer with the absence of intermediate hierarchic levels. Besides the traditional concentration of equipment and services, with scarce intermediate-level healthcare centers (as occurs in the Northeast), the North region is also affected by a scarce occupation of the territory, which is negatively reflected on the organization and distribution of the offer of health services (25,26) . The unequal allocation of resources, concentration of health professionals in urban centers, and the lack of investments in resources and infrastructure lead to the reproduction of socioeconomic inequalities in the assistance of individuals with cancer (24) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these data, it is estimated that by 2025, there will be a significant increase in mortality from PC in the North and Northeast, followed by a decrease in other regions of the country. 21 Such information is explained due to the influence of the regionspecific social, economic and geographic aspects that interfere with access to specialized services and the temporal widening between diagnosis and treatment. 22 It is mentioned that the chances of progressing to a lethal outcome are higher when patients are hospitalized.…”
Section: Discussionmentioning
confidence: 99%